Two Trees - Cochrane, John H.; Longstaff, Francis A.; Santa-Clara, Pedro (Review of Financial Studies, 2008)
We solve a model with two i.i.d. Lucas trees. Although the corresponding one-tree model produces a constant price-dividend ratio and i.i.d. returns, the two-tree model produces interesting asset-pricing dynamics. Investors want to rebalance their portfolios after any change in value. Because the size of the trees is fixed, prices must adjust to offset this desire. As a result, expected returns, excess returns, and return volatility all vary through time. Returns display serial correlation and are predictable from price-dividend ratios. Return volatility differs from cash-flow volatility, and return shocks can occur without news about cash flows.